2009
DOI: 10.1103/physrevlett.102.205001
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Electromagnetic Fields and Plasma Flow in Hohlraums with Proton Radiography

Abstract: We report on the first proton radiography of laser-irradiated hohlraums. This experiment, with vacuum gold (Au) hohlraums, resulted in observations of self-generated magnetic fields with peak values $10 6 G. Time-gated radiographs of monoenergetic protons with discrete energies (15.0 and 3.3 MeV) reveal dynamic pictures of field structures and plasma flow. Near the end of the 1-ns laser drive, a stagnating Au plasma ($10 mg cm À3 ) forms at the center of the hohlraum. This is a consequence of supersonic, radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 22 publications
2
50
1
Order By: Relevance
“…Since SRS and TPD only occur in underdense plasmas, ≤ n c /4 and n c /4, respectively, where n c is the critical density, these mechanisms would require a large-volume ablated low-density gold plasma. Since previous proton radiography experiments showed that the timescale for hohlraum wall motion 19 is longer than the E field generation time 18 , SRS and TPD in the ablated wall plasma cannot explain the data.…”
mentioning
confidence: 43%
See 3 more Smart Citations
“…Since SRS and TPD only occur in underdense plasmas, ≤ n c /4 and n c /4, respectively, where n c is the critical density, these mechanisms would require a large-volume ablated low-density gold plasma. Since previous proton radiography experiments showed that the timescale for hohlraum wall motion 19 is longer than the E field generation time 18 , SRS and TPD in the ablated wall plasma cannot explain the data.…”
mentioning
confidence: 43%
“…8) we conclude that these fast protons cannot be produced by any LPI mechanism at the LEH window. This production mechanism is therefore associated with the general hohlraum charging, as discovered using charged-particle radiography 18 , which creates E fields of order 10 9 V/m. Such strong fields can create runaway ions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only data from the equator (DIM 90-78) is shown. This is because the polar yield data is affected by transverse electromagnetic field structures at the LEH, which can cause deflections and thus a reduction in the apparent yield observed by the WRFs on the pole [34][35][36] . A significant shot-to-shot yield variation is observed, i.e.…”
Section: Nif Experimentsmentioning
confidence: 99%